Revision of Carpal Tunnel Release due to Palmaris Longus Profundus - Lyrtzis Christos; Natsis Konstantinos; Pantazis Evagelos (Case Reports in Orthopedics)
Purpose. The palmaris longus profundus has been documented throughout the literature as a cause of carpal tunnel syndrome. We present a case of palmaris profundus tendon removal during the revision of carpal tunnel release. Method. During a carpal tunnel release in a 66-year-old woman, palmaris profundus tendon was found inside the tunnel under the transverse carpal ligament, just above the median nerve, but it was left intact. The patient complained of pain in the hand at night and weakness of her hand one month after surgery. We decided on a revision of the carpal tunnel release. The palmaris profundus tendon was found and was removed. Results. The patient had a normal postoperative course. Two months later she returned to her normal activities and was asymptomatic. Conclusions. When a palmaris profundus muscle is located in carpal tunnel, we recommend its excision during carpal tunnel release. This excision will eliminate the possibility of recurrent compression over the median nerve.